Case report: Successful treatment of OXA-23 Acinetobacter baumannii neurosurgical infection and meningitis with sulbactam-durlobactam combination therapy - Jacob W. Snowdin; Nicholas J. Mercuro; Michael P. Madaio; Stephen A. Rawlings (Frontiers in Medicine, 2024)
Meningitis caused by Acinetobacter species is a rare complication of neurosurgical procedures, although it is associated with high morbidity and mortality. Carbapenem-resistant Acinetobacter is particularly difficult to treat, considering the limited selection and tolerability of effective antimicrobials. Sulbactam-durlobactam was approved by the FDA in 2023 for treatment of hospital-acquired and ventilator-associated pneumonia due to susceptible strains of Acinetobacter, including carbapenem-resistant Acinetobacter baumannii. Here, we present a case of carbapenem-resistant Acinetobacter baumannii neurosurgical infection and meningitis successfully treated with sulbactam-durlobactam combination therapy.